Malignant stroke in an adolescent with a homozygous MTHFR 677CT mutation and intake of hormonal contraceptives - Pfurtscheller, K.; Senning, B.; Bernhard, H.; Novak, M.; Zobel, G.; Plecko, B.; Muntean, W. (Hämostaseologie, 2009)
Severe stroke in children and adolescents with its devastating long term consequences remains a rare disorder with many open questions. Beside the well known risk factors such as infection or congenital and acquired heart disease, coagulation disorders have to be considered in the differential work up of the underlying aetiology. Here we report the case of an adolescent with a homozygote MTHFR 677CT mutation suffering a malignant stroke shortly after the start of oral contraceptives. Conclusion: Since prevention seems easily feasible, general screening for MTHFR mutations might be worthwhile in women before starting oral contraceptives.
Keywords: Stroke; children; methylenetetrahydrofolate reductase; hormonal contraceptives